2014
DOI: 10.1152/ajpcell.00174.2013
|View full text |Cite
|
Sign up to set email alerts
|

Glucose stimulates calcium-activated chloride secretion in small intestinal cells

Abstract: The sodium-coupled glucose transporter-1 (SGLT1)-based oral rehydration solution (ORS) used in the management of acute diarrhea does not substantially reduce stool output, despite the fact that glucose stimulates the absorption of sodium and water. To explain this phenomenon, we investigated the possibility that glucose might also stimulate anion secretion. Transepithelial electrical measurements and isotope flux measurements in Ussing chambers were used to study the effect of glucose on active chloride and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Recently, Yin et al showed that glucose may regulate the expression of ANO1 [16]. Therefore, we analyzed mRNA expression of ANO1 and other candidates involved in chloride secretion, including anoctamin 6 (ANO6), the purinergic receptor P2Y2R, the Na + -K + -Cl − cotransporter 1 (NKCC1), and CFTR in the presence of low and high glucose in the embryonic kidney cyst model (Fig.…”
Section: High Glucose Leads To Increased Transcriptional Regulation Omentioning
confidence: 99%
“…Recently, Yin et al showed that glucose may regulate the expression of ANO1 [16]. Therefore, we analyzed mRNA expression of ANO1 and other candidates involved in chloride secretion, including anoctamin 6 (ANO6), the purinergic receptor P2Y2R, the Na + -K + -Cl − cotransporter 1 (NKCC1), and CFTR in the presence of low and high glucose in the embryonic kidney cyst model (Fig.…”
Section: High Glucose Leads To Increased Transcriptional Regulation Omentioning
confidence: 99%
“…Additionally, this part of the study may give some new indications that RSV may affect Ca 2+ -induced Cl − secretion since the glucose-induced I sc for ctrl/Cl − -free chambers was decreased compared to ctrl/Cl − chambers (p = 0.014). It has been shown that glucose stimulates Ca 2+ -induced Cl − secretion in intestinal cells [26, 27]. Therefore, this difference may indicate that a part of the ΔI sc under control conditions may be due to glucose-mediated stimulation of Ca 2+ -induced Cl − secretion especially since there is a correlation between the glucose-induced ΔI sc under ctrl and Cl − -free conditions (R 2  = 0.846, p = 0.0004).…”
Section: Resultsmentioning
confidence: 98%
“…We recently found that electrolytes, glucose, and some amino acids are poorly absorbed in the GI tract following irradiation. In addition, we observed that glucose and some amino acids can stimulate electrogenic Cl − secretion in addition to Na + absorption and can increase paracellular permeability, which further complicates radiation-induced diarrhea and increased gut permeability2030. Increased paracellular permeability is known to increase translocation of antigenic substances from the gut lumen into the systemic compartment, causing an increase in pro-inflammatory cytokines20.…”
Section: Discussionmentioning
confidence: 99%